PENEGAKAN HUKUM YANG BERORIENTASI PADA KEBERLANJUTAN SUMBER DAYA IKAN - Rochmani, Rochmani (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2014)
AreaÂ ofÂ IndonesiaÂ consists ofÂ 80% water, whichÂ containsÂ abundanceÂ ofÂ potentialÂ fishÂ resources,Â ThoseÂ fish resourcesÂ shouldÂ beÂ utilizedÂ forÂ as muchÂ asÂ prosperityÂ and welfareÂ forÂ Indonesian.Â InÂ fact,Â fishÂ resourceshavenât enhanced theÂ livingÂ standard, whichÂ isÂ sustainable and equitable.Â Issues on fisheries come up such as exaggerationÂ ofÂ fishing,Â theftÂ fish,Â illegalÂ fishingÂ activitiesÂ andÂ theÂ useÂ ofÂ fishÂ resourcesÂ thatÂ exceedingÂ thegeneration of fishÂ itself. ThatÂ circumstance willÂ cause harmÂ forÂ the state,Â the fishermen, as well as peopleÂ in general.Â TheÂ useÂ ofÂ toolsÂ thatÂ harmÂ theÂ nature willÂ causeÂ theÂ decreaseÂ ofÂ fishÂ resourcesÂ andÂ threatÂ thesustainabilityÂ ofÂ fishÂ resources.Â TheÂ aimÂ ofÂ writingÂ thisÂ articleÂ isÂ toÂ analyzeÂ lawÂ enforcementÂ relatedÂ toÂ the sustainability of fishÂ resources and the sustainability ofÂ fishÂ resources, viewed fromÂ the perspective ofÂ justice.As the result ofÂ the study,Â law enforcement to protect theÂ fish resources generally has not given attentionÂ to theÂ sustainability ofÂ fishÂ resources,Â thereforeÂ fishermenÂ stillÂ useÂ unfriendlyÂ toolsÂ toÂ catchÂ theÂ fishes.Â ThoseunfriendlyÂ tools willÂ causeÂ theÂ occurrenceÂ ofÂ over-fishingÂ and willÂ impactÂ toÂ theÂ environmentalÂ damages. ThoseÂ kinds ofÂ things will destructÂ theÂ fishes,Â thereforeÂ theÂ quantityÂ ofÂ fish willÂ have deteriorated and evencouldÂ beÂ extinct.Â ThoseÂ environmentalÂ damages wouldÂ sufferÂ theÂ present generationÂ as wellÂ asÂ theÂ next generationÂ sinceÂ theyÂ couldnâtÂ consumeÂ fish whichÂ isÂ veryÂ essentialÂ forÂ theÂ growthÂ ofÂ the human bodyÂ anderadicateÂ the job for the people as the fishermen. The present generation will be sinful if the next generation will getÂ theÂ impact of whatÂ the present generation done.Â In orderÂ toÂ reduce more over-fishing activities and theÂ distrustÂ ofÂ theÂ fish habitatÂ itÂ needsÂ theÂ lawÂ enforcement, whichÂ is orientedÂ toÂ theÂ sustainability ofÂ fish resources.Â TheÂ sustainabilityÂ ofÂ fisheryÂ resourcesÂ couldnât maintainÂ itsÂ existence,Â thisÂ couldÂ beÂ seenÂ asÂ the symbolÂ ofÂ environmentalÂ damages.Â InÂ thisÂ case,Â theÂ lawÂ alsoÂ needsÂ to makeÂ integrationÂ ofÂ fishÂ resources sustainability to be processed so thatÂ it willÂ result outputÂ law enforcement which is oriented toÂ fish resourcessustainability.Â AsÂ aÂ conclusion,Â inÂ lawÂ enforcementÂ orientedÂ toÂ fishÂ resourcesÂ sustainability,Â itÂ needsÂ toÂ be thought by the lawmaker to embed that the law should containÂ idea or concept about justice,Â legal certainty,the significance of fish resources and the implementation of the law itself. In the fish resources utilization and law enforcements, it needs to pay attention to the justice principle; intergenerational equity; intergenerational equity;Â precautionary;Â conservationÂ ofÂ biologicalÂ diversity;Â conservationÂ ofÂ biologicalÂ diversity.